2021
DOI: 10.1097/ec9.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 induced renal injury differs from that in other viral-infections

Abstract: Background:Kidney injuries caused by several viral diseases have been reported worldwide among all age groups, races, and genders. Of particular importance is coronavirus disease 2019 (COVID-19), and its prevalence in communities infecting all patient populations with symptoms ranging from asymptomatic to severe, including complications and mortality.Methods:Data were acquired from PubMed, Scopus, Google Scholar, Centers for Disease Prevention and Control (CDC), and Lexi-Comp using the following search terms: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(164 reference statements)
0
3
0
Order By: Relevance
“…Skin rashes and discolored toes can also occur in COVID-19 infection, dependent on the patient’s age. [8] The pathology is not well understood. There are many ophthalmic complications, such as conjunctivitis, episcleritis, itchy eyes, and blurry vision, likely due to cytokine release syndrome or local invasion and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin rashes and discolored toes can also occur in COVID-19 infection, dependent on the patient’s age. [8] The pathology is not well understood. There are many ophthalmic complications, such as conjunctivitis, episcleritis, itchy eyes, and blurry vision, likely due to cytokine release syndrome or local invasion and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the RBD and N-terminal domain regions result in enhanced affinity of the spike protein binding to angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) receptors, which supplements viral attachment and entry into the host cells for infection. [8] A preprint reported 50 genetic mutations of Omicron, with 15 mutations occurring in the RBD of the spike protein, which binds to the ACE2 receptor for viral entry. [9] Experimental microscale thermophoresis data from this study further confirmed that the RBD mutations in Omicron are associated with a 5-fold higher binding affinity to ACE2 compared with the RBD of the original SARS-CoV-2 virus.…”
Section: Introductionmentioning
confidence: 99%
“…Direct cytopathic effects of a replicating virus, inflammation-induced cell injury from infiltrating inflammatory cells, acute tubule necrosis and podocyte damage contribute to protein leakage from the Bowman’s capsule and occurrence of collapsing glomerulopathy ( 43 ). COVID-19 infection can activate complement (C5b-9) deposition at the brush borders of apical tubules, leading to cell apoptosis, tubulointerstitial damage and impairment of renal function ( 44 , 45 ). Cytotoxic particles such as perforin, granulysin released by activated killer lymphocytes and leukocyte-derived proinflammatory cytokines such as interleukin-1, interleukin-6 and tumor necrosis factor-alpha, further lead to a cytokine storm.…”
Section: Discussionmentioning
confidence: 99%